Dark Energy - Li, Miao ... [et al.]. (Singapore ; World Scientific Pub. Co., 2015)
This book introduces the current state of research on dark energy. It consists of three parts. The first part is for preliminary knowledge, including general relativity, modern cosmology, etc. The second part reviews major theoretical ideas and models of dark energy. The third part reviews some observational and numerical works. The aim of this book is to provide a sufficient level of understanding of dark energy problems, so that the reader can both get familiar with this area quickly and also be prepared to tackle the scientific literature on this subject. It will be useful for graduate students and researchers who are interested in dark energy.
pt I. Preliminaries in a nutshell. 1. Gravitation. 1.1. The curved spacetime. 1.2. The curved spacetime : an example. 1.3. The Einstein equation -- 2. Matter components. 2.1. The stress tensor. 2.2. Perfect fluid. 2.3. Observers and energy conditions. 2.4. The vacuum. 2.5. Particles. 2.6. Homogeneous field configurations -- 3. Cosmology. 3.1. The cosmological principle. 3.2. Newtonian cosmology. 3.3. FRW Cosmology -- pt. II. Theoretical aspects. 4. Introduction to dark energy. 4.1. The cosmological constant reloaded. 4.2. The theoretical challenge -- 5. Weinberg's classification. 5.1. Supersymmetry. 5.2. Anthropic principle. 5.3. Tuning mechanism. 5.4. Modifying gravity. 5.5. Quantum cosmology -- 6. Symmetry. 6.1. Supersymmetry in 2 + 1 dimensions. 6.2. 't Hooft-Nobbenhuis symmetry. 6.3. Kaplan-Sundrum symmetry. 6.4. Symmetry of reversing sign of the metric. 6.5. Scaling invariance in D [symbol] 4 -- 7. Anthropic principle. 7.1. Bousso-Polchinski scenario. 7.2. KKLT scenario. 7.3. Populating the landscape and anthropic interpretations -- 8. Tuning mechanisms. 8.1. Brane versus bulk mechanism. 8.2. Black hole self-adjustment -- 9. Modified gravity. 9.1. f(R) Models. 9.2. MOND and TeVeS theories. 9.3. DGP model. 9.4. Other modified gravity theories -- 10. Quantum cosmology. 10.1. Cosmological constant seesaw. 10.2. Wave function through the landscape -- 11. Holographic principle. 11.1. The holographic principle. 11.2. Holographic dark energy. 11.3. Complementary motivations. 11.4. Agegraphic dark energy. 11.5. Ricci dark energy -- 12. Back-reaction. 12.1. Sub-hubble inhomogeneities. 12.2. Super-hubble inhomogeneities -- 13. Phenomenological models. 13.1. Quintessence, phantom and quintom. 13.2. K-essense, custuton, braiding and ghost condensation. 13.3. Higher spin fields. 13.4. Chaplygin gas and viscous fluid. 13.5. Particle physics models. 13.6. Dark energy perturbations -- 14. The theoretical challenge revisited -- pt. III. Observational aspects. 15. Basis of statistics. 15.1. [symbol] analysis. 15.2. Algorithms for the best-fit analysis. 15.3. The Markov chain Monte Carlo algorithm. 15.4. The Fisher matrix techniques -- 16. Cosmic probes of dark energy. 16.1. Type Ia supernovae. 16.2. Cosmic microwave background. 16.3. Baryon acoustic oscillations. 16.4. Weak lensing. 16.5. Galaxy clusters. 16.6. Gamma-ray burst. 16.7. X-ray observations. 16.8. Hubble parameter measurements. 16.9. Cosmic age tests. 16.10. Growth factor. 16.11. Other cosmological probes -- 17. Dark energy projects. 17.1. On-going projects. 17.2. Intermediate-scale, near-future projects. 17.3. Larger-scale, longer-term future projects -- 18. Observational constraints on specific theoretical models. 18.1. Scalar field models. 18.2. Chaplygin gas models. 18.3. Holographic dark energy models. 18.4. Dvali-Gabadadze-Porrati model. 18.5. f(R) models. 18.6. Other modified gravity models. 18.7. Inhomogeneous LTB and back-reaction models. 18.8. Comparison of dark energy models -- 19. Dark energy reconstructions from observational data. 19.1. Specific Ansatz. 19.2. Binned parametrization. 19.3. Polynomial fitting. 19.4. Gaussian process modeling.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Dark energy (Astronomy); Electronic books